On genre-format approaches in the process of defining the phenomenon of "multimedia journalism" - Safaryan, Arman (Bulletin of Yerevan University B: Philology, 2022)
The article examines the terms “Internet journalism” (digital journalism), “convergent journalism” and “multimedia journalism”, often used as “synonymous terms” to denote new forms of journalistic activity, in connection with the use of the Internet by journalists as a platform for disseminating information. The traditional genres of journalism are being “revised” to reveal their potential “coverage” of multimedia phenomena. It is proposed to define the concept of “multimedia journalism” through the prism of genre-format approaches, as despite the existing methodological differences in the scientific literature regarding genre-forming and format-forming features, the mutually transitive nature of the processes of multimedization and the new genre-format solutions have become obvious.